CRISPR‐enabled point‐of‐care diagnostics for early cancer detection - Pan, Yuwei; Xu, Qihang; Spatola Rossi, Carla; Yang, Zhugen (Wiley, 2026)
Cancer is the leading cause of death worldwide, accounting for nearly 10 million deaths in 2020. The early diagnosis of cancer biomarkers is essential for improving prognosis and reducing the global disease burden. However, conventional diagnostic methods depend on sophisticated instrumentation, well‐trained personnel, and complex workflows, which is usually time‐consuming and costly. With programmable and sequence‐specific nucleic acid recognition and cleavage, clustered regularly interspaced short palindromic repeats (CRISPR)‐Cas systems have emerged as powerful tools for disease diagnostics. Their integration with engineering approaches, such as microfluidic devices including paper‐based microfluidics, electrochemical, and smartphone‐enabled platforms, has further enhanced cost‐effectiveness, portability, and automation. This review presents the molecular mechanisms of CRISPR‐Cas systems, recent advances in point‐of‐care testing (POCT) and its compatible technologies, and their applications in early cancer detection. We also discuss key challenges and future directions to enable accessible and reliable CRISPR‐enabled diagnostics for improved global cancer diagnostics and provide the potential solution for effective treatment.
Keywords: biosensors; cancer diagnostics; CRISPR-Cas; early detection; POCT